AKUNTABILITAS SEKOLAH; SUATU UPAYA MENINGKATKAN MUTU PENDIDIKAN MADRASAH - Maryono Maryono (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
It is not wrong if many people have a bad image of islamic education in this time. Because of the islamic education has less a good quality, low of society participation in developing a school, and less of networking in the global. Therefore, it needs a new step in managing the school that is an accountability. Accountability was assumpted able to increase the quality of education of madrasah. This article was aimed ; a) to know the concept of educational accountability, b) to understand the concept of educational quality, and to know the implication of implementing the educational accountabilitiy for islamic education.